Efek Pemanis Buatan Sakarin Dan Sari Buah Naga Merah (Hylocereus costaricensiss) Terhadap Histopatologi Hati Dan Ginjal Mencit (Mus musculus L.) - Sari, Ela Santi Mulya; Sudiastuti, Sudiastuti; Sudrajat, Sudrajat (BIOPROSPEK: Jurnal Ilmiah Biologi, 2016)
This study aims to determine the effects of saccharin and dragon fruit juice on histopatologic of liver and kidney and determine the effective dose of dragon fruit juice to improve the cells of liver and kidney mice (Mus musculus L.) after fed saccharin. The study design used was completely randomized design (CRD). In this study, the independent variables consist of two control and three treated treatment with 5 replications. The histological data of liver and kidneys of mice (Mus musculus L.) presented descriptively,and evaluation of differences in the structure of the liver and kidney mikroanatomi saccharin and dragon fruit (Hylocereus polyrhizus) be compared to normal structure. The results showed that administration of saccharin at a dose of 15mg/kg BB/day to given effect on the histopathology of kidney and liver of mice. Treatment of the red dragon fruit juice at a dose of 200mg/Kg BB/day may improve liver and kidney mikroanatomi structures damaged by the provision of saccharin. From this research, showed that the red dragon fruit juice swetened with saccharin can inhibition effects of on structure microanatomy the liver and kidney